Thermal performance of new type plate heat exchanger with spring turbulence generator using nanofluid flow - Peker, Gokce; Yildiz, Cengiz; Cakmak, Gulsah; Bilgic, Yusuf; Yildiz, Ahmet (Taylor & Francis Inc, 2023)
In this study, a new design has been developed to increase the thermal performance of a plate heat exchanger. In the developed design, springs are placed on the heat exchanger plates at an angle of 45 degrees. In this study, which aims to improve heat transfer by increasing turbulence, nanoparticles were also used to increase the heat transfer coefficient of the heat transfer fluid. The nanoparticles used are Al2O3 and CuO in three different densities. The performance factor of the system was calculated experimentally with these fluids entering the heat exchanger at six different speeds. The highest performance factor obtained was 1.33, and it was obtained by using 1% mass ratio Al2O3 nanoparticles. The highest value for CuO, the other nanoparticle used, was determined as 1.27. The highest increases in heat transfer are 60.7% and 56.5% for Al2O3 and CuO, respectively.
Keywords: Plate heat exchanger; nanofluid; turbulent flow; spring channel; heat exchangers